Functional analysis of the Escherichia coli K-12 cyn operon transcriptional regulation. - Lamblin, A F (1994)
The cynTSX operon enables Escherichia coli K-12 to degrade and use cyanate as a sole nitrogen source. The promoter of this operon is positively regulated by cyanate and the CynR protein. CynR, a member of the LysR family of regulatory proteins, binds specifically to a 136-bp DNA fragment containing both the cynR and the cynTSX promoters. In this study, we report the results of DNase I digestion studies showing that CynR protects a 60-bp region on the cynR coding strand and a 56-bp sequence on the cynTSX coding strand. CynR binding was not affected by cyanate or its structural homolog azide, a gratuitous inducer of the operon. However, CynR-induced bending of two different DNA fragments was detected. The amount of bending was decreased by cyanate.